Pengaruh person organization fit dan modal psikologi terhadap komitmen organisasional melalui kepuasan kerja - Wijiati, Wahyu; Priyono, Bambang Suko (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of person organization fit and psychological capital on organizational commitment through job satisfaction. Indications of the problem found a decline in the community satisfaction survey at the end of 2020 with good conditions showing the performance of the Class III Port Management Unit Office of Batang Regency is still experiencing instability since the survey was conducted with the online system. The data collection technique was done through purposive sampling with a sample size of 97 employees. The analysis was performed using multiple linear regression to measure the influence of person organization fit and psychological capital on organizational commitment through job satisfaction. In knowing the indirect effect, the Sobel test was carried out. The results showed that Person organizational fit had no effet on organizational commitment, Person organizational fit had an effect on job satisfaction, Psychological Capital had an effect on Organizational Commitment, Psychological Capital had an effect on Organizational Commitment, Job Satisfaction had an effect on Organizational Commitment, Person Organizational Fit on Organizational Commitment through Job Satisfaction. and Psychological Capital has an effect on Organizational Commitment through Job Satisfaction.